Understanding the lie of the land: an institutional analysis of petro-governance in Tanzania. Issue 1 (2nd January 2018) - Lee, Bryan; Dupuy, Kendra
Abstract : Tanzania has recently discovered large petroleum and natural gas reserves, boosting its natural resource stocks and potential future revenue flows. Whether the country's petroleum resources will translate into economic development will be determined by the institutions that the government puts into place to govern the petroleum sector, to include the legal institutions. This study reviews the most important provisions of the new legislative framework that the government has recently adopted to govern this newfound wealth. We examine the institutions and actors created by the legislation as well as the opportunities and challenges that may emerge in its future implementation. Specifically, we analyse the petro-sector institutions that the legislation creates and the types of authorities granted to them; the institutional constraints placed on authorities; the interaction between institutions; potential institutional overlaps, conflicts and gaps; and transparency and accountability mechanisms.